Association of family history of tumors with clinicopathological characteristics and prognosis of colorectal cancer. Issue 4 (July 2019) - Shan, Tao; Chen, Shuo; Chen, Xi; Lin, Wanrun; Li, Wei; Ma, Jiancang; Wu, Tao; Cui, Xijuan; Li, Wang; Kang, Ya'an; Yang, Wenbin
Abstract : To investigate the association of family history of malignant tumors with clinicopathological characteristics of colorectal cancer, and its effects on prognosis. We conducted a retrospective review of pathological and follow-up data of patients with colorectal cancer treated in our hospital from January 2010 to December 2015. Of 870 patients undergoing surgery, 737 received follow-up (84.7%). Among them, 192 (26.1%) were family history of malignant neoplasm-positive [MN-FH (+)] and 545 (73.9%) were family history of malignant neoplasm-negative [MN-FH (–)]. MN-FH (+) patients had earlier disease onset, smaller tumor diameter, lower rate of lymph node metastasis, and lower depth of invasion. There were significant differences in BMI between the groups ( P <0.05) but no differences in sex or tumor differentiation grade ( P >0.05). Rates of Her-2 and p53 protein expression in MN-FH (+) patients were 34.3 and 40.5%, respectively, compared with 22.2 and 26.3% in MN-FH (–) patients. In stage 3, significantly higher Her-2 and p53 protein expression rates were observed in MN-FH (+) than in MN-FH (–) patients. Fluorescence in-situ hybridization showed significantly higher Her-2 expression in MN-FH (+) than in MN-FH (–) patients. The 3 and 5-year overall survival, disease-free survival, and progression-free survival were significantly lower in MN-FH (+) than in MN-FH (−) patients ( P <0.05). MN-FH (+) patients with colorectal cancer had earlier disease onset and smaller tumor area, lower invasion depth, a lower rate of lymph node metastasis, and earlier TNM tumor stage at diagnosis than MN-FH (–) patients. BMI value distribution significantly differed between groups. However, long-term prognosis was worse for MN-FH (+) than MN-FH (–) patients, suggesting that internal pathogenic genes play a more crucial role than external environmental factors in prognosis. Family history of tumors could be an independent prognostic factor for colon cancer.